Climatic Factor Differences and Mangosteen Fruit Quality between On- and Off-Season Productions - Krisanadej Jaroensutasinee; Mullica Jaroensutasinee; Piyatida Boonsanong (Ital Publication, 2023)
The objective of this study was to investigate the differences in climatic factors and fruit quality between on- and off-season production periods. Climate, soil, and mangosteen measurements were all studied during on- and off-season production. We chose 40 mangosteen trees and observed flowering and fruit set rates over two production periods. The results showed that the number of flowers per branch, the number of fruits per branch, the circumference of fruits, and the fruit weight were higher during the on-season mangosteen production period than during the off-season mangosteen production period. However, the number of edible pulp segments, peel thickness, percentage of translucent flesh, and fruit gumminess were lower in the on-season mangosteen production period than in the off-season mangosteen production period. The percentage of fruit scars did not differ between the on- and off-season mangosteen production periods. When compared to the on-season mangosteen production period, there was lower relative humidity, soil moisture at 120 cm depth, and leaf wetness at 15 cm above ground during the off-season mangosteen production period; however, there was higher air temperature, soil moisture, and soil temperature at all four depth levels. Doi: 10.28991/ESJ-2023-07-02-020 Full Text: PDF